Minimasi Biaya Masalah Penjadwalan Awak Pesawat Menggunakan Teknik Penugasan - Elis Ratna Wulan; Aa Mujtaba; Rima Mutia (Universitas Pendidikan Indonesia (UPI), 2023)
In this paper, the problem of airline crew scheduling is studied. The main difficulties are divided into team missions and team mixes based on their sheer size, initial arrangement, and flexible rules and directions of airport locations. In this paper, we propose the problem in which flight schedules and crew schedules for aircraft are optimally fixed through data provision. Then, we construct a mathematical model by determining the transportation cost from all flight schedules for a given time period to not disturb crew members with available crews. The model is solved using the Hungarian method. From the present study undertaken, the optimum solution for the given cost between Bhubaneshwar and Kolkata flight routes was observed as 85 hours.Keywords: Flight Crew Scheduling, Hungarian Method, Minimum Cost. AbstrakPada makalah ini, dikaji permasalahan penjadwalan kru maskapai. Kendala utama dari masalah penjadwalan kru adalah pembagian tugas berkelompok, pencampuran tim berdasarkan ukurannya yang besar, dan penataan awalnya, serta peraturan dan pedoman fleksibel dari posisi bandara. Dalam makalah ini, diusulkan masalah di mana jadwal penerbangan dan jadwal kru pesawat difiksasi secara optimal dengan memberikan data. Kemudian, dibangun model matematika dengan membatasi biaya transportasi dari semua penjadwalan penerbangan dari periode waktu tertentu untuk tidak mengganggu anggota kru dengan kru yang tersedia. Model tersebut diselesaikan dengan metode Hungarian. Dari studi kasus yang diambil, solusi optimal dari biaya maskapai yang diberikan antara rute kru Bhubaneswar dan Kolkata tercatat sebesar 85 jam.